Respuesta :
the last choice is right sure because this is a perfect square trinomial
(4xy -3z)^2 = 16x^2y^2 -24xyz +9z^2
hope this will help you
(4xy -3z)^2 = 16x^2y^2 -24xyz +9z^2
hope this will help you
Answer:
Option D is correct
[tex]16x^2y^2-24xyz+9z^2[/tex]
a perfect square trinomial
Step-by-step explanation:
Using a perfect square trinomial:
[tex](a-b)^2 = a^2-2ab+b^2[/tex] ....[1]
Given the expression:
[tex](4xy-3z)^2[/tex]
let a = 4xy and b = 3z
then;
Substitute in [1] we have
[tex](4xy-3z)^2 = (4xy)^2-2(4xy)(3z)+(3z)^2[/tex]
Simplify:
[tex](4xy-3z)^2 =16x^2y^2-24xyz+9z^2[/tex]
Therefore, the expression which is equivalent to [tex](4xy-3z)^2[/tex] is [tex]16x^2y^2-24xyz+9z^2[/tex] and type of special product is: perfect square trinomial